A Randomized Controlled Trial Examining the Efficacy of Motivational Counseling with Observed Therapy for Antiretroviral Therapy Adherence - Goggin, Kathy (Springer US, 2013)
This study determined whether motivational interviewing-based cognitive behavioral therapy (MI-CBT) adherence counseling combined with modified directly observed therapy (MI-CBT/mDOT) is more effective than MI-CBT counseling alone or standard care (SC) in increasing adherence over time. A three-armed randomized controlled 48-week trial with continuous electronic drug monitored adherence was conducted by randomly assigning 204 HIV-positive participants to either 10 sessions of MI-CBT counseling with mDOT for 24 weeks, 10 sessions of MI-CBT counseling alone, or SC. Poisson mixed effects regression models revealed significant interaction effects of intervention over time on non-adherence defined as percent of doses not-taken (IRR = 1.011, CI = 1.000–1.018) and percent of doses not-taken on time (IRR = 1.006, CI = 1.001–1.011) in the 30 days preceding each assessment. There were no significant differences between groups, but trends were observed for the MI-CBT/mDOT group to have greater 12 week on-time and worse 48 week adherence than the SC group. Findings of modest to null impact on adherence despite intensive interventions highlights the need for more effective interventions to maintain high adherence over time.